Muslim Students’ Perception of Green Economy Education in Promoting Ethical and Sustainable Economic Awareness - Lady Eka Rahmawati; Eliza Noviriani; Elshad Yusifov (International Forum of Researchers and Lecturers, 2024)
Global environmental challenges require active engagement from all sectors, including education. For Muslim youth, awareness of environmental sustainability aligns with Islamic ethical principles such as stewardship (khalifah), justice (ʿadl), and social welfare (maslahah). This study examines the influence of green economy education within Islamic higher education on students’ eco-literacy, ethical awareness, and sustainable economic behavior. A quantitative approach was employed using a structured questionnaire distributed to students from both Islamic economics and non-economics programs. Data were analyzed with descriptive statistics, independent t-tests, and one-way ANOVA to identify differences in environmental knowledge, attitudes, and behavior. Findings show that students with an Islamic economics background consistently achieve higher scores in knowledge, attitudes, and behavioral engagement related to sustainability compared to non-Islamic economics students. Integrating Islamic ethical values into the curriculum provides a holistic framework for internalizing sustainability principles, encouraging students to translate ethical knowledge into practical action. Pedagogical strategies such as project-based learning, reflective exercises, and experiential programs further enhance engagement and eco-conscious behavior. The study highlights the critical role of Islamic education in fostering a generation of ethically aware and environmentally responsible students. By embedding moral and ecological principles in academic programs, educational institutions can strengthen students’ capacity for sustainable decision-making and support broader goals of responsible economic and environmental stewardship.